Can you afford to be ill : hospital service plan (London : The London Association for Hospital Services Limited)
1945 1945 1940s 15 pages : illustrations What is the Hospital Service Plan? The Hospital Service Plan has been prepared with the general approval of the voluntary hospitals, and the Council has had the advantage of collaboration with the British Medical Association to ensure its being acceptable to the medical profession as well as to the voluntary hospitals. The Hospital Service Plan is not run for profit, and its solvency is guaranteed by King Edward's Hospital Fund for London. It endeavours to provide the greatest possible benefits in return for a small contribution and to allocate them so that they will help you with your most likely needs. You or your registered dependants are entitled to a grant towards the cost of an aggregate period of six weeks In-Patient treatment in any membership year. The schedule of benefits is clearly stated on pages 7 and 8, and a study of them will show that it is possible to receive grants totalling as much as £105. By doubling your subscription you become entitled to double benefit. This grant is payable towards accounts for In-Patient service and maintenance in hospital pay-beds and recognised nursing 3 292/842/2/63